Analisis Inovasi Layanan Anak ”Kurenah Storytelling” Terhadap Peningkatan Kunjungan Pemustaka Di Perpustakaan Daerah Kota Padang Panjang - Rika Jufriazia Manita; Fega Nurhidayati (Jurnal Ilmu Perpustakaan dan Informasi Islam, 2022)
The main problem in this thesis is the interest of visiting users in children's services at the Padang Panjang City Library. The purpose of this study was to determine whether the innovation of children's services "KURENAH storytelling" influenced the interest of visiting users at the Regional Library of Padang Panjang City. This type of research is a fielresearch with qualitaative descriptive memethodsThe research was conducted at the Regional Library of Padang Panjang City with primary data sources being library managers and parents who came to visit the Regional Library of Padang Panjang City. Data obtained from interviews and documentation, the research method used is descriptive qualitative analysis. The results of the study show that the effect of implementing the child service innovation "KURENAH storytelling" on increasing user visits at the Padang Panjang City Library is assessed from several indicators, namely good service, facilities and infrastructure provided, attractiveness (promotion), and safety of the places visited. From these indicators, it can be seen that the increase in user visits at the Padang Panjang City Library has proven that the implementation of the child service innovation "KURENAH storytelling" has an effect on increasing user visits, but there is one indicator that is less influential due to the current Covid-19 condition.Keywords: Innovation, Children's services, Storytelling, Interest in visiting